2022
DOI: 10.1038/s41598-022-21690-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of spike protein of SARS-CoV-2 and its variant Omicron (B.1.1.529) on some immune characteristics

Abstract: The emergence of Omicron variant raises great concerns because of its rapid transmissibility and its numerous mutations in spike protein (S-protein). S-protein can act as a pathogen-associated molecular pattern and complement activator as well as antigen. We compared some immune characteristics of trimer S-proteins for wild type (WT-S) and B.1.1.529 Omicron (Omicron-S) to investigate whether the mutations have affected its pathogenicity and antigenic shift. The results indicated that WT-S and Omicron-S directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition, Omicron BA.1 infected patients showed a low systemic inflammatory response compared to patients infected with previous SARS-CoV-2 variants ( 44 ). Mechanistically, the direct comparison of the B.1 S protein with the BA.1 S protein revealed that the BA.1 S protein induced less activation of immune modulators, such as NF-κB ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Omicron BA.1 infected patients showed a low systemic inflammatory response compared to patients infected with previous SARS-CoV-2 variants ( 44 ). Mechanistically, the direct comparison of the B.1 S protein with the BA.1 S protein revealed that the BA.1 S protein induced less activation of immune modulators, such as NF-κB ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of SARS-CoV-2 structural proteins have been conducted in vitro using an array of human and mouse cells. Both the S protein or it’s S1 subunit is sufficient to elicit a proinflammatory immune response in primary cells and cell lines including human lung cells ( Forsyth et al, 2022 , Khan et al, 2021 , Patra et al, 2020 ), human endothelial cells ( Perico et al, 2022 ), human intestinal epithelial cells ( Forsyth et al, 2022 ), HL-60 cells ( Zhao et al, 2021 ), human monocytes/macrophages ( Karwaciak et al, 2021 , Khan et al, 2021 , Pantazi et al, 2021 , Schroeder and Bieneman, 2022 , Shirato and Kizaki, 2021 , Zhao et al, 2021 ), mouse macrophages ( Li et al, 2022 , Shirato and Kizaki, 2021 , Zhao et al, 2021 ), human peripheral blood mononuclear cells ( Olajide et al, 2021b ), and TF1PIGA null cells ( Yu et al, 2020 ). Interestingly, Zhao and colleagues examined the proinflammatory effects of different domains of the S protein and found that the N-terminal (NT) and receptor binding (RB) domains (D) failed to elicit a proinflammatory cytokine response.…”
Section: Sars-cov-2 Glycoproteins Function As Pampsmentioning
confidence: 99%
“…However, Li et al conducted a comparison of the proinflammatory properties between the S protein of the original isolate and the Omicron (B.1.1.529) variant. They found that the Omicron S variant produced a weaker inflammatory response compared to the original isolate ( Li et al, 2022 ). Otherwise, it is largely unknown to what extent mutations in the S and S1 subunit of variants affect the proinflammatory properties of these proteins.…”
Section: Sars-cov-2 Glycoproteins Function As Pampsmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinctly, we typically found larger alterations in samples challenged with 20 ng/mL of the recombinant protein as compared to those where the lower 2 ng/mL concentration was added, as well as in those especially challenged with SARS-CoV-2 recombinant spike protein of the Alpha and Delta variants. Thus, it is conceivable that the sequence and structure of these two spike protein variants may display better affinity for some receptors expressed at monocyte surface and/or may be capable to more intensely trigger monocyte activation and injury compared to the Omicron spike protein, as was earlier conjectured [35]. The lower chemical stability of the Omicron spike protein compared to the spike protein of former variants the has also been suggested as an important characteristic that may explain the lower pathogenetic burden of this strain [36].…”
Section: Discussionmentioning
confidence: 85%